Local Respiratory Allergy: From Rhinitis Phenotype to Disease Spectrum - Testera-Montes, Almudena; Salas, Maria; Palomares, Francisca; Ariza, Adriana; Torres, María J.; Rondón, Carmen; Eguiluz-Gracia, Ibon (Frontiers in Immunology, 2021)
Local respiratory allergy (LRA) is defined by the negativity of atopy tests, a clinical history suggestive of airway allergy and a positive response to the nasal and/or bronchial allergen challenge. The clinical spectrum of LRA is comprised of three conditions: local allergic rhinitis (LAR) and local allergic asthma in non-atopic patients, and dual allergic rhinitis (coexistence of allergic rhinitis and LAR) in atopic individuals. LRA is an independent disease phenotype not progressing to atopy over time, but naturally evolving to the clinical worsening and the onset of comorbidities. Published data suggests that LRA is mediated through the mucosal synthesis of allergen-specific (s)IgE, which binds to FcϵRI on resident mast cells, and in >50% of cases traffics to the blood stream to sensitize circulating basophils. To date, 4 clinical trials have demonstrated the capacity of allergen immunotherapy (AIT) to decrease nasal, conjunctival and bronchial symptoms, to improve quality of life, to increase the threshold dose of allergen eliciting respiratory symptoms, and to induce serum sIgG4 in LRA individuals. Collectively, these data indicate that local allergy is a relevant disease mechanisms in both atopic and non-atopic patients with airway diseases.